2015
DOI: 10.1021/acs.jpcc.5b04882
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Zeolite Catalysts for Soot Oxidation: Influence of Hydrothermal Aging

Abstract: Developments in diesel engines and gasoline direct injection (GDI) engines have spawned the requirement of soot oxidation catalysts that work well in both NO+O 2 and O 2 . In this study, we found that supporting Pt on zeolites such as H-ZSM5 and USY may receive better soot oxidizers than commercial Pt/Al 2 O 3 catalyst. Durability tests indicate that even after the hydrothermal ageing at 800 ºC, the aged Pt/H-ZSM5 is still a better soot oxidizer than Pt/Al 2 O 3 in NO+O 2 , and the aged Pt/USY exhibits the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 40 publications
(224 reference statements)
1
18
0
Order By: Relevance
“…Liu et al reported that the acid properties of the catalyst play a key role in the oxidation of soot. 27,28 Acid sites can convert soot particles into active carbon cation radicals. These cation radical intermediates are highly active and can be oxidized by molecular oxygen at lower temperatures.…”
Section: Redox and Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al reported that the acid properties of the catalyst play a key role in the oxidation of soot. 27,28 Acid sites can convert soot particles into active carbon cation radicals. These cation radical intermediates are highly active and can be oxidized by molecular oxygen at lower temperatures.…”
Section: Redox and Acidmentioning
confidence: 99%
“…CeO 2 -containing materials have been widely used in heterogeneous catalysis, for tasks such as the purification of car exhaust emissions, removal of organics in wastewater, combustion of volatile organic compounds, as well as diesel soot oxidation. The unique ability of Ce to switch between 4+ and 3+ oxidation states, along with the resulting oxygen vacancy defects which balance the charge in the cerium oxide lattice are sources of active sites for various catalytic applications including diesel soot oxidation. In addition, few studies have investigated the importance of acid properties of the catalysts for soot oxidation. , The acid sites can convert soot particles into active carbon radical cation species, which can be easily oxidized by O 2 . Although Ce-, Cu- and Fe-oxides show mild acid properties, nanostructuring, shape selectivity, and metal/oxide interfaces in Cu/CeO 2 rods and Fe/CeO 2 rods may enhance the acid properties that can show a favorable effect in diesel soot oxidation.…”
Section: Introductionmentioning
confidence: 95%
“…The combined effect of water and nitrogen monoxide for Pt-based catalysts during replace soot combustion is analogous to the platinum catalytic behaviour in carbon black oxidation under similar conditions. 22,37 This can be explained by the interaction of water with nitrogen monoxide and dioxide, which results in the formation of nitric and nitrous acids as intermediates and nitronium ions (NO 2 + ) in acids, which easily react with soot and cause the hydrolysis of oxygenated species formed on the soot surface during oxidation. 22,[37][38][39]…”
Section: Effect Of H 2 O and No On The Catalyst Activitymentioning
confidence: 99%
“…Recently, Pt/H-ZSM-5 was reported for soot combustion by Liu et al . 18 , 19 , who found that the acidic ZSM-5 support inhibited NO 2 adsorption. However, owing to the high price of noble metals, K-promoted oxide catalysts have attracted much attention 20 23 .…”
Section: Introductionmentioning
confidence: 99%